CD-340 Functionalized Doxorubicin-Loaded Nanoparticle Induces Apoptosis and Reduces Tumor Volume Along with Drug-Related Cardiotoxicity in Mice [Corrigendum] - Mondal L (Dove Medical Press, 2021)
Mondal L, Mukherjee B, Das K, et al. Int J Nanomedicine. 2019;14:8073–8094.The authors have advised due to an error at the time of figure assembly, Figure 5 on page 8085 is incorrect. The correct Figure 5 is shown below. The authors apologize for this error and advise it does not affect the results of the paper.Read the original article